Pemberdayaan Perempuan Pesisir Pantai Muara Abu Kupang melalui Pelatihan Olah Sampah Plastik Bernilai Ekonomis dan Berdaya Guna - Gusnawati, Gusnawati; Jasron, Jahirwan Ut; Jafri, Muhamad; Sanusi, Arifin (Faculty of Engineering UNHAS, 2024)
Waste is anything that is no longer used from all human activities, where, if not managed properly, it can hurt the surrounding community, including waste dumped into water channels such as rivers, which carry the waste to the sea and pollute the sea. Plastic waste is included in it. The amount of this waste continues to increase over time. The use of equipment made of plastic because it is light, unbreakable, flexible, practical, economical, and can replace the function of other items, such as use for drinking water packaging, food containers, and others, encourages increased production of plastic waste. Skills are needed in processing and converting this plastic waste into goods that have economic value and are helpful, especially for residents who live around rivers and coastal areas, including on the coast of Muara Abu Beach, West Oesapa. Therefore, this service aims to provide practical solutions by providing skills to women on the coast of Muara Abu Beach who have a profession as scavengers who join PKH Kasih Dua RT. 001/RW 001, Oesapa Barat Village, Kupang City, to implement waste bank management and plastic waste processing techniques that cannot be deposited into the waste bank, namely with a plastic waste shredder machine, so that residual waste has economic value. The implementation of community service using interview and training methods related to waste bank management and the use of plastic waste shredder machines. The pre-test and post-test results of community service participants showed that 65% of the participant's knowledge of the activity material was an essential reason for the sustainability of similar programs for other community environments. It is hoped that activities like this can provide solutions to problems related to waste around the partner's residence.